Counted cycles method to measure the block inception time of kiloHertz frequency mammalian motor nerve block - Bhadra, N (J Neurosci Methods, 2019)
BACKGROUND: Kilohertz frequency alternating currents (KHFAC) produce rapid nerve conduction block of mammalian peripheral nerves and have potential clinical applications in reducing nerve hyperactivity. However, there are no experimental measurements of the block inception time (BIT) for the complete block of mammalian motor axons, i.e. the time from the start of delivery of the KHFAC to the axons reaching a fully blocked state. NEW METHOD: A “counted cycles” method (CCM) was designed to exploit characteristics of the onset response, which is typical of KHFAC block, to measure the BIT with a millisecond time resolution. Randomized and repeated experiments were conducted in an in-vivo rodent model, using trains of KHFAC over a range of complete cycle counts at three frequencies (10, 20, and 40 kHz). RESULTS: Complete motor nerve conduction block was obtained in the rat sciatic nerve (N=4) with an average BIT range of 5 ms to 10 ms. The fastest BIT measured was 2.5 ms to 5 ms. There was no statistical difference between the block inception times for the three frequencies tested. COMPARISON WITH EXISTING METHODS: There are no comparable methods to measure the KHFAC BIT. CONCLUSION: The KHFAC BIT is faster than previously estimated. KHFAC motor nerve block is established in milliseconds. These results may assist in the design of methods to eliminate the onset response produced by KHFAC nerve block.